Wiskott-Aldrich syndrome gene as a prognostic biomarker correlated with immune infiltrates in clear cell renal cell carcinoma - Ding, Guixin; Wang, Tianqi; Liu, Shangjing; Zhou, Zhongbao; Ma, Jian; Wu, Jitao (Frontiers in Immunology, 2023)
The abnormal expression of the Wiskott-Aldrich syndrome protein (WASP) encoded by the Wiskott-Aldrich syndrome (WAS) gene has been implicated in tumor invasion and immune regulation. However, prognostic implications of WAS and its correlation tumor infiltrating in renal clear cell carcinoma (ccRCC) is not clear cut. Using The Cancer Genome Atlas (TCGA), Gene Expression Omnibus (GEO), Tumor Immune Estimation Resource (TIMER), UALCAN, Gene Expression Profiling Interaction Analysis (GEPIA), Kaplan-Meier (KM) plotter and other databases, the correlation between WAS expression, clinicopathological variables and clinical outcomes was evaluated. In addition, quantitative polymerase chain reaction (qPCR) verified elevated level of WAS expression in ccRCC compared with adjacent normal tissues. Furthermore, we assessed the transcription expression of WAS in various renal carcinoma cell lines and human renal tubular cells (HK2) using qPCR and found that WAS protein expression was highly expressed in cancer tissues, particularly within renal tumor cells via the human protein atlas (HPA). A comprehensive analysis of multiple databases including TIMER, GEPIA, TISIDB, ESTIMATE algorithm, and CIBERSORT algorithm was performed to determine the correlation between WAS and tumor infiltrating immune cells in ccRCC. Interestingly, we had found that elevated WAS expression was significantly positively correlated with the infiltration of CD8 T cells, B cells, Monocytes, Neutrophils, Macrophages, T cell regulation, NK cells, and Dendritic cells in renal clear cell carcinoma. Bioinformatics demonstrated a strong correlation between WAS expression and the T cell exhaustion gene PD-1, which is critical for exploring immunotherapy for ccRCC. Our next step was to examine the relationship between WAS expression and 42 immune checkpoints. In conclusion, our study identified that WAS was a prognostic biomarker and correlated with immune infiltrates in ccRCC.